A novel method to quantify cutaneous vascular innervation. Issue 4 (5th May 2020) - Sohn, Eunhee; Suh, Bum Chun; Wang, Ningshan; Freeman, Roy; Gibbons, Christopher H.
Abstract: Introduction: To develop a new method to quantify the density of nerves, vessels, and the neurovascular contacts, we studied skin biopsies in diabetes and control subjects. Methods: Skin biopsies with dual immunofluorescent staining were used to visualize nerves and blood vessels. The density of nerves, vessels, and their neurovascular contacts were quantified with unbiased stereology. Results were compared with examination findings, validated questionnaires, and autonomic function. Results: In tissue from 19 controls and 20 patients with diabetes, inter‐rater and intra‐rater intraclass correlation coefficients were high (>0.85; P  < .001) for all quantitative methods. In diabetes, the nerve densities ( P  < .05), vessel densities ( P  < .01), and the neurovascular densities ( P  < .01) were lower compared with 20 controls. Results correlated with autonomic function, examination and symptom scores. Discussion: We report an unbiased, stereological method to quantify the cutaneous nerve, vessel and neurovascular density and offer new avenues of investigation into cutaneous neurovascular innervation in health and disease. Abstract : See editorial on pages 427–429 in this issue .